I know a shy fellow who swallowed a cello - Garriel, Barbara Schmitz; O'Brien, John, 1953- (Honesdale, Pa. : Boyds Mills Press, 2012)
The song "I know an old lady who swallowed a fly" provides inspiration for this story of a shy person who literally develops an appetite for musical instruments ranging from popular to classical and from large to small.
Reprint. Originally published: 2004.
1-2
Keywords: Musical instruments -- Fiction; Stories in rhyme